Edukasi Ecopreneurship dan Praktik Pembuatan Lulur Organik Beras Ketan Hitam di SMA N 9 Samarinda - Sianturi, Sister; Hanindita, Shafira (Jurnal Pengabdian Masyarakat Hutan, 2025)
Ecopreneurship, or environment-based entrepreneurship, offers a strategic approach to thematic training aimed at fostering environmental awareness and entrepreneurial skills. This study presents a training program conducted at SMA Negeri 9 Samarinda, which introduced high school students to ecopreneurship through the development of an organik body scrub made from black glutinous rice. The program consisted of two core components: (1) theoretical instruction on organik products and ecopreneurship concepts, and (2) hands-on practice in creating the body scrub. Effectiveness was assessed through pre- and post-training evaluations, which revealed a significant increase in student knowledge—from an average pre-test score of 64.11 to a post-test average of 78.75. Students exhibited strong engagement and active participation throughout the sessions. They also developed and presented simple promotional posters for their products, promoting soft skills such as public speaking and creative visual design. This initiative demonstrates the potential of ecopreneurship education to inspire interest in environmental sustainability and creative entrepreneurship among youth